(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
To handle huge amounts of data, either a single user or organization are depending on the cloud environment but security to their data is the major concern that the cloud service provider has to take care of in the public clouds during the process of outsourcing. So, the cloud environments have deployed a component known as “Third Party Auditor”, which verifies the data in the cloud and ensures that the data is not tampered with by the attackers. While interacting with the public cloud, every user has a period known as the “verification period”, during which the user can raise the data challenge task to the auditor. In general, the data uploaded by the user are divided into various blocks or segments. Hence, to verify a single user data the auditors have to generate multiple integrity reports and should check their consistency. If TPA detects any inconsistent data, then it has the right to reject the process and notifies the same user but the major problem is TPA works simultaneously with more users because of which the verification process becomes a burden to the TPA. If the system is overloaded with more verification requests then the cost of computing in the cloud increases and the time to check the data integrity also increases which results in compromise by the TPA. So, to address this issue many researchers have proposed integrity verification algorithms but most of them suffer from many design issues like resource allocations, relay time decisions, and time consumption hence the proposed system has implementeda cuckoo algorithm integrated with AES to generate the keys and performs bilinear map functions to repair and audit within an optimal time